Microglia at the blood brain barrier in health and disease - Mayer, Meredith G.; Fischer, Tracy (Frontiers in Cellular Neuroscience, 2024)
The blood brain barrier (BBB) plays a crucial role in maintaining brain homeostasis by selectively preventing the entry of substances from the peripheral blood into the central nervous system (CNS). Comprised of endothelial cells, pericytes, and astrocytes, this highly regulated barrier encompasses the majority of the brain's vasculature. In addition to its protective function, the BBB also engages in significant crosstalk with perivascular macrophages (MΦ)s and microglia, the resident MΦ of the brain. These interactions play a pivotal role in modulating the activation state of cells comprising the BBB, as well as MΦs and microglia, themselves.Alterations in systemic metabolic and inflammatory states can promote endothelial cell dysfunction, reducing the integrity of the BBB and potentially allowing peripheral blood factors to leak into the CNS compartment. This may mediate activation of perivascular MΦs, microglia, and astrocytes, and initiate further immune responses within the brain parenchyma, suggesting neuroinflammation can be triggered by signaling from the periphery, without primary injury or disease originating within the CNS. The intricate interplay between the periphery and the CNS through the BBB highlights the importance of understanding the role of microglia in mediating responses to systemic challenges. Despite recent advancements, our understanding of the interactions between microglia and the BBB is still in its early stages, leaving a significant gap in knowledge. However, emerging research is shedding light on the involvement of microglia at the BBB in various conditions, including systemic infections, diabetes, and ischemic stroke. This review aims to provide a comprehensive overview of the current research investigating the intricate relationship between microglia and the BBB in health and disease. By exploring these connections, we hope to advance our understanding of the role of brain immune responses to systemic challenges and their impact on CNS health and pathology. Uncovering these interactions may hold promise for the development of novel therapeutic strategies for neurological conditions that involve immune and vascular mechanisms.